(untitled) (Orinoquia, 2021)
In recent years, the presence of emerging contaminants (ECs) in the environment has been the subject of multiple studies, thus becoming a central research topic. ECs are made up of different groups of compounds, including drugs, endocrine disruptors, plasticizers and hormones. When they enter aquatic systems, they are easily transported and distributed in the different water sources and, due to their characteristics, they become a major environmental problem, since they can accumulate in different species. The objective of this study was to evaluate the presence of eight ECs, ibuprofen (IBF), gemfibrozil (GEM), triclosan (TCS), carbamazepine (CBZ), caffeine (CAF), bisphenol A (BPA), ethinylestradiol (EE2) and progesterone (PROG) in water from the Doctrina and Mocarí irrigation districts, Córdoba - Colombia, which irrigate different crops along their course. The detection and quantification of ECs was carried out by high-performance liquid chromatography with diode array detector and molecular flourescence (HPLC-DAD- FLD). BPA was detected in all the water samples analyzed with an average of 0.036 μg/L, TCS was the compound found in highest concentration with 97.27 μg/L, followed by PROG with 35.17 μg/L and CBZ with 23.46 μg/L. The presence of the ECs detected is evidence of the anthropogenic pressure exerted on these irrigation districts; the concentrations found could represent an environmental risk in the future and compromise agricultural activities in the region given the capacity of these compounds to accumulate in the crops.